Characterization of Electromagnetic Wave Absorbers with Broadside SRR Method on C-Band - Dwi Banyu Prawito; Rasheed Abdurrahman Mulyadi; Budi Syihabuddin; Levy Olivia Nur (IJITEE (International Journal of Information Technology and Electrical Engineering), 2020)
Electromagnetic wave absorber is a material that can reduce the energy available in electromagnetic waves. Electromagnetic wave absorber can be used to reduce interference in wireless communication devices so as not to quickly suffer damage, as a layer in the room free of reflection and to reduce radar cross section of an object detected in radar tracking applications. In this paper, a discussion about the use of the broadside form using the Split Ring Resonator (SRR) method as an absorber of electromagnetic waves and its characteristics in C-Band. Broadside shape is obtained from the initial form of a square which is developed into a square resonator and then given a gap at the end of the resonator. The results show that the SRR broadside form can be used as an absorbent of electromagnetic waves on the C-Band, precisely the frequency of 6.41 GHz with absorption rates reaching 99.99% and bandwidth of 0.077 GHz with dimensions of 7 mm. From the experimental results, it can also be seen that the change in the gap length variable in the SRR broadside shape is the most influential in changing the resonant frequency value and the amount of bandwidth produced.